Pressure injury related to the use of personal protective equipment in COVID-19 pandemic - Manuela de Mendonça Figueirêdo Coelho; Viviane Mamede Vasconcelos Cavalcante; Juliano Teixeira Moraes; Luciana Catunda Gomes de Menezes; Sarah Vieira Figueirêdo; Mírian Ferreira Coelho Castelo Branco; Solange Gurgel Alexandre (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To describe the prevalence and factors associated with pressure injuries related to the use of personal protective equipment during the COVID-19 pandemic. Methods: Cross-sectional study conducted using an instrument made available in social networks with 1,106 health professionals. The data were analyzed using descriptive statistics and compared, considering pvalue < 0.05. Results: There was a prevalence of 69.4% for pressure injuries related to the use of personal protective equipment, with an average of 2.4 injuries per professional. The significant factors were: under 35 years of age, working and wearing personal protective equipment for more than six hours a day, in hospital units, and without the use of inputs for protection. Conclusion: Pressure injuries related to the use of medical devices showed a high prevalence in this population. The recognition of the damage in these professionals makes it possible to advance in prevention strategies.